Outer membrane protein YadA of enteropathogenic yersiniae mediates specific binding to cellular but not plasma fibronectin. - Schulze-Koops, H (1993)
The binding of bacteria or bacterial products to host proteins of tissue extracellular matrix may be a mechanism of tissue adherence. We investigated interactions of the plasmid-encoded outer membrane protein YadA, which confers pathogenic functions on enteropathogenic yersiniae, with fibronectin. Attachment of YadA-positive and YadA-negative recombinant Yersinia enterocolitica strains to cartilage-derived human cellular fibronectin and human plasma fibronectin in the solid phase revealed that YadA mediates binding of yersiniae to cellular fibronectin in a saturable, concentration-dependent manner. The interaction could be inhibited by an anti-YadA-specific anti-serum. An anti-beta 1-integrin antibody and the synthetic peptide G-R-G-D-S-P, representing the binding site for alpha 5 beta 1-integrin on fibronectin, did not block attachment of YadA-positive yersiniae to cellular fibronectin, indicating a binding site for YadA on cellular fibronectin independent of the R-G-D-S-containing site. By contrast, YadA failed to mediate binding to plasma fibronectin immobilized on nitrocellulose or plastic surfaces. These observations provide evidence for the hypothesis that the binding region for YadA in cellular fibronectin is not present in plasma fibronectin. This study is the first report on differential binding of bacteria to splicing variants of fibronectin. Further experiments might answer the question whether binding of YadA to cellular fibronectin contributes to the pathogenesis of yersiniae, both to the initial adhesion of the bacteria to the matrices of the host and to the arthritogenic potential of enteropathogenic yersiniae.